Crambescin C1 Exerts a Cytoprotective Effect on HepG2 Cells through Metallothionein Induction - Roel, María (Mar Drugs, 2015)
The Mediterranean marine sponge Crambe crambe is the source of two families of guanidine alkaloids known as crambescins and crambescidins. Some of the biological effects of crambescidins have been previously reported while crambescins have undergone little study. Taking this into account, we performed comparative transcriptome analysis to examine the effect of crambescin-C1 (CC1) on human tumor hepatocarcinoma cells HepG2 followed by validation experiments to confirm its predicted biological activities. We report herein that, while crambescin-A1 has a minor effect on these cells, CC1 protects them against oxidative injury by means of metallothionein induction even at low concentrations. Additionally, at high doses, CC1 arrests the HepG2 cell cycle in G0/G1 and thus inhibits tumor cell proliferation. The findings presented here provide the first detailed approach regarding the different effects of crambescins on tumor cells and provide a basis for future studies on other possible cellular mechanisms related to these bioactivities.